Student participation rate in their learning self-assessment - Liliam Barrios Herrero; Eduardo de Jesús Pomares Bory; Dayamí Maza Ares (Medisur)
Foundation: self-assessment contributes to the self-regulation of learning by students, so it is convenient to monitor this activity. Objective: to analyze the students’ participation rate from the Miguel Enríquez, 10 de Octubre and Salvador Allende Medical Sciences Faculties, in their learning self-assessment from the subject Cells, Tissues and Integumentary System, during the 2023-2024 academic year. Methods: a descriptive, cross-sectional research with a mixed approach was developed. Theoretical methods were used: analysis-synthesis, inductive-deductive and logical history; empirical: documentary review and content analysis; as well as the statistical mathematician. Results: the data analysis obtained allowed us to classify the students’ participation rate in the self-assessment of their learning as very low in the Miguel Enríquez and 10 de Octubre Medical Sciences Faculties, and low in Salvador Allende. A significantly positive Spearman correlation index was determined between the students’ participation index and their schools of origin (p < 0.001), in six of the eight self-assessment activities considered, with a tendency to higher index values in the Salvador Allende faculty. Conclusions: the research carried out made it possible to determine the existence of limitations regarding the students’ participation in the self-assessment of their learning, in the subject Cells, Tissues and Integumentary System, whose degree is related to the origin faculties.